O Eu de Augusto dos Anjos: a ciência, a filosofia e o prosaico como elementos da fatura estética - Alex Alves Fogal (2016)
The scientific vocabulary and the philosophic concept use in Augusto dos Anjos poetry is usually pointed out. However, it hasnt been studied systematically yet, intending to comprehend the importance of this particularity in poetic form, developed by this author. Something similar occurs with the prosaic aspect of his composition, generally interpreted as a simple freaky detail or puerile volition to shock the target public.This paper proposal is demonstrating this three devices the science, the philosophy, and the prosaic - arranged in Augusto dos Anjos poetry organically, constituting a solid and reflexive aesthetic scheme, whose place in Brazilian literary tradition is well defined.